2010
DOI: 10.17161/fec.v43i2.6691
|View full text |Cite
|
Sign up to set email alerts
|

The U.S. Supreme Court and Parental Rights under the Individuals with Disabilities Education Act

Abstract: President Gerald Ford signed the Education for All Handicapped Children Act (EAHCA) into law in 1975. Since the original passage of the EAHCA, the law has been amended four times and renamed the Individuals with Disabilities Education Act (IDEA) (See Figure 1). After each revision, the U.S. Department of Education has issued new regulations implementing the Act (IDEA Regulations, 34 C.F.R. § 300 et seq). The current IDEA, as amended, is codified in Title 20 of the United States Code (IDEA, 20 U.S.C. § § 1400 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Recent case law has also underscored the importance of parental participation (see Conroy, Yell, Katsiyannis, & Collins, 2010;Yell, Katsiyannis, & Losinski, 2013…”
Section: Definitions Of Parent or Guardian In Legislationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent case law has also underscored the importance of parental participation (see Conroy, Yell, Katsiyannis, & Collins, 2010;Yell, Katsiyannis, & Losinski, 2013…”
Section: Definitions Of Parent or Guardian In Legislationmentioning
confidence: 99%
“…Recent case law has also underscored the importance of parental participation (see Conroy, Yell, Katsiyannis, & Collins, 2010; Yell, Katsiyannis, & Losinski, 2013). For example, in Doug C. v. Hawaii Department of Education (2013), the 9th Circuit Court found that IDEA-mandated timelines for individualized education program (IEP) revisions or reevaluations are considered secondary in importance to having parents in attendance and that the IEP meeting should have been rescheduled unless the parent refused to attend (see also 34 C.F.R.…”
Section: Definitions Of Parent or Guardian In Legislationmentioning
confidence: 99%
“…President Gerald Ford signed the Education for All Handicapped Children Act (EAHCA) in 1975, and it has been amended four times over 29 years. It was renamed the Individuals with Disabilities Education Act (IDEA) in 1990 and the Individuals with Disabilities Education Improvement Act (IDEIA) in 2004 (Conroy, Yell, Katsiyannis, & Collins, 2010) (Table 1). As a federal law, the federal courts have jurisdiction for IDEA claims once exhaustion of other remedies has failed.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of federal law through the hearing of cases by the Supreme Court sets precedents when conflicts exist in interpretation of the law. This is according to stare decisis, or common law doctrine (Conroy et al, 2010). In 2010, one case regarding autism and IDEIA was appealed to the Supreme Court of the United States but the writ of certiorari was denied.…”
Section: Introductionmentioning
confidence: 99%